Thrombolytic Failure with Streptokinase in Acute Myocardial Infarction Using Electrocardiogram Criteria: Thrombolytic Failure with Streptokinase in Acute Myocardial Infarction - Farooq, Maria; Abdullah, Sadaf; Khalil, Hadiqa; Sarfraz, Juneda; Ahmed, Nisar; Shahzad, Hamid (Pakistan Journal of Health Sciences, 2025)
Streptokinase remains a key thrombolytic agent for ST-elevation myocardial infarction (STEMI) in many low-resource settings. Understanding the rate of thrombolytic failure and its predictors using electrocardiographic criteria is important for optimizing therapeutic strategies. Objectives: To determine the rate of thrombolytic failure in acute myocardial infarction using streptokinase, to describe in-hospital outcomes, and to assess associations between baseline clinical and ECG variables and thrombolytic success. Methods: This prospective observational study was conducted at Lady Reading Hospital, Peshawar. Ninety-three consecutive adult STEMI patients treated with streptokinase within 12 hours of symptom onset were included. Successful reperfusion was defined as >50% ST-segment resolution at 90 minutes. Demographics, risk factors, MI type, Killip class, symptom-to-door categories, and in-hospital outcomes were recorded. Bleeding events were classified using the TIMI criteria. Data were analyzed using the t-test for continuous variables and the chi-square/Fisher’s exact test for categorical variables, with p < 0.05 considered significant. Results: The thrombolytic success rate was 77.4%. Symptom-to-door categories (<3h, 3–6h, >6h) were not significantly associated with reperfusion success. No baseline risk factors or Killip class independently predicted outcome. In-hospital mortality was 2.2%, TIMI major bleeding was 2.2%, and minor bleeding was 6.5%. Rescue PCI was required in 15.1%. Persistent chest pain, reperfusion arrhythmias, and hemodynamic instability occurred in 16.1%, 17.2%, and 14.0% respectively. Conclusion: Streptokinase achieved a high reperfusion rate with low complication rates. Conventional baseline variables did not predict success. Emphasis should remain on early presentation, system-level efficiency, and timely rescue PCI for failures.